Bamboo particle reinforced polypropylene composites made from different fractions of bamboo culm: Fiber characterization and analysis of composite properties. Issue 12 (12th June 2019) - Tan, Wei; Hao, Xiaolong; Fan, Qi; Sun, Lichao; Xu, Junjie; Wang, Qingwen; Ou, Rongxian
Abstract: Differences in anatomical structure and chemical composition of bamboo fractions have an obvious influence on the properties of bamboo thermoplastic composites (BPCs). Six fractions of bamboo particles including bamboo culm (BC), bamboo green (BG), bamboo timber (BT), bamboo yellow (BY), bamboo node (BN), and bamboo processing residue (BR) were prepared and compounded with polypropylene (PP) to fabricate BPCs using extrusion. The anatomical structure, chemical composition, crystallinity, and morphology of the bamboo particles were characterized. The processability, mechanical properties, creep‐recovery, and dynamic viscoelasticity of the BPCs were evaluated. The results show that the anatomical structure and composition of the bamboo fractions influenced the crystallinity, morphology, and aspect ratio (L/D) of the bamboo particles, as well as the performance of the resulting composites. BG had the largest crystallinity, length, and L/D, followed by BC and BT. BY was the shortest with the smallest L/D. The BC/PP composites exhibited the best processability and optimal mechanical properties. The BG/PP composites had the highest modulus and creep resistance. The BY/PP composites had the poorest processability and mechanical performance. These results indicate that BG from processing residues can be recycled into high‐value composites and provide a scientific basis for further research on BPCs made from bamboo processing residues.